Peran Penyuluh Pertanian dalam Mendorong Adopsi Teknologi Alsintan pada Petani Padi di Kecamatan Simpang Kabupaten Ogan Komering Ulu Selatan - Doka Apda; Munajat Munajat; Enda Kartikasari; Fifian Permata Sari (LPPM Institut Pendidikan Nusantara Global, 2026)
Agricultural mechanization has become one of the primary strategies for improving rice productivity and supporting sustainable agricultural development in Indonesia. Despite continuous government assistance in providing agricultural machinery (ALSINTAN), the adoption rate among rice farmers remains relatively low. Agricultural extension workers play a strategic role in accelerating technology adoption through their functions as facilitators, motivators, and educators. This study aimed to analyze the influence of these three extension roles on farmers' decisions to adopt agricultural machinery technology in Simpang District, Ogan Komering Ulu Selatan Regency, South Sumatra, Indonesia. The study employed a quantitative research design involving 167 rice farmers selected through multistage purposive sampling. Primary data were collected using structured questionnaires, while logistic regression analysis was employed to determine the influence of each extension role on farmers' adoption decisions. The findings indicate that agricultural extension workers significantly contribute to improving farmers' willingness to adopt agricultural machinery by facilitating access to technology, increasing farmers' motivation, and strengthening their technical knowledge and skills. These findings demonstrate that strengthening agricultural extension services is essential for accelerating agricultural modernization and improving the sustainability of rice farming systems.